Factors influencing clinical pharmacists’ integration into the clinical multidisciplinary care team - Wang, Chenyu; Li, Maozhen; Huang, Yuankai; Xi, Xiaoyu (Frontiers in Pharmacology, 2023)
Objectives: To investigate the factors influencing clinical pharmacists’ integration into the clinical multidisciplinary care team, using interprofessional collaboration between clinical pharmacists and physicians as the focus. Methods: Through stratified random sampling, a cross-sectional questionnaire survey was conducted among clinical pharmacists and physicians in secondary and tertiary hospitals in China from July to August 2022. The questionnaire, comprising the Physician–Pharmacist Collaborative Index (PPCI) scale to reflect the collaboration level and a combined scale to measure influencing factors, was made available in two versions for clinical pharmacists and physicians. Multiple linear regression was adopted to analyze the association between the collaboration level and influencing factors, as well as the heterogeneity of the significant factors in hospitals of different grades. Results: Valid self-reported data from 474 clinical pharmacists and 496 paired physicians were included, who were serving in 281 hospitals from 31 provinces. In terms of participant-related factors, standardized training and academic degree, respectively, exerted significant positive effects on the perceived collaboration level by clinical pharmacists and physicians. In terms of context characteristics, manager support and system construction were the main factors for improving collaboration. In terms of exchange characteristics, clinical pharmacists having good communication skills, physicians trusting others’ professional competence and values, and both parties having consistent expectations had significant positive effects on collaboration. Conclusion: The study provides a baseline data set on the current level and associated factors of clinical pharmacists’ collaboration with other professionals in China and other countries with a related health system, providing references for individuals, universities, hospitals, and national policymakers to facilitate the development of clinical pharmacy and multidisciplinary models and further improve the patient-centered integrated disease treatment system.